Deep neural networks based on gating mechanism for open-domain question answering - Arch Tijera, Drake Christian (2018)
I would like to thank in a special way the National Council of Science, Technology and Technological Innovation (CONCYTEC) and the National Fund for Scientific, Technological development and Technological Innovation (FONDECYT-CIENCIACTIVA), which through the Management Agreement N 234-2015-FONDECYT, they have allowed the grant and financing of my studies of Master in Computer Science at the Universidad Cat´olica San Pablo (UCSP).